2017
DOI: 10.1111/his.13380
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathology of thyroid tumours of follicular cells: a review of genetic alterations and their clinicopathological relevance

Abstract: Thyroid cancer is the most common endocrine malignancy. Knowledge of the molecular pathology of thyroid tumours originating from follicular cells has greatly advanced in the past several years. Common molecular alterations, such as BRAF p.V600E, RAS point mutations, and fusion oncogenes (RET-PTC being the prototypical example), have been, respectively, associated with conventional papillary carcinoma, follicular-patterned tumours (follicular adenoma, follicular carcinoma, and the follicular variant of papillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
97
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 229 publications
(433 reference statements)
4
97
0
8
Order By: Relevance
“…RAS mutations are the most common to indeterminate nodules and have been found in both benign and malignant nodules, presenting an uncertain PPV ranging from 15% to 70%. 28,[31][32][33][34][35][36][37][38][39][40][41][42] Furthermore, PPARG-and THADA-related fusion transcripts can have RAS-like properties, 15 while other fusions such as those related to NTRK and ALK have properties that are neither RAS-like nor BRAFV600E-like. Rare BRAF mutations, excluding BRAFV600E, have RAS-like properties rather than BRAFV600E-like properties, and have been found in both benign and malignant thyroid nodules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RAS mutations are the most common to indeterminate nodules and have been found in both benign and malignant nodules, presenting an uncertain PPV ranging from 15% to 70%. 28,[31][32][33][34][35][36][37][38][39][40][41][42] Furthermore, PPARG-and THADA-related fusion transcripts can have RAS-like properties, 15 while other fusions such as those related to NTRK and ALK have properties that are neither RAS-like nor BRAFV600E-like. Rare BRAF mutations, excluding BRAFV600E, have RAS-like properties rather than BRAFV600E-like properties, and have been found in both benign and malignant thyroid nodules.…”
mentioning
confidence: 99%
“…15,26,27 Although PIK3CA and PTEN mutations have been reported in follicular thyroid cancer, poorly differentiated thyroid cancers, and anaplastic thyroid cancer, [28][29][30] they can also be found in benign thyroid adenomas, as can GNAS and ALK mutations and THADA-and PPARG-related fusions. 28,[31][32][33][34][35][36][37][38][39][40][41][42] Furthermore, PPARG-and THADA-related fusion transcripts can have RAS-like properties, 15 while other fusions such as those related to NTRK and ALK have properties that are neither RAS-like nor BRAFV600E-like. 15 Although the predictive value for malignancy of these oncogenic changes is not well understood when found individually, it is well established that coexistence of many of these oncogenic changes along with other oncogenic drivers is generally associated with aggressive forms of thyroid cancer and poor prognosis.…”
mentioning
confidence: 99%
“…The identification of vascular and/or capsule invasion on intraoperative frozen sections is challenging. Till date, no single molecule detection method reliably distinguishes between FTA and FTC, but FTA is known to transform into FTC, owing to many common mutations in genes such as the RAS . FTAs with molecular changes such as a PAX8‐PPARG rearrangement are considered to be precursors to FTC .…”
Section: Discussionmentioning
confidence: 99%
“…27 FTAs with molecular changes such as a PAX8-PPARG rearrangement are considered to be precursors to FTC. 27,28 Third, thyroid nodules with high thyroglobulin levels are not found exclusively in FTC. On analysis of the nodular thyroid in false-positive events, we found that both the nodule diameter and thyroglobulin levels were higher in the cases of nodular goitre with cystic changes than in the other two types of nodular goitre.…”
Section: Discussionmentioning
confidence: 99%
“…The benign counterpart of follicular carcinoma is follicular adenoma, and it is often challenging to differentiate them by cytology. Follicular adenomas (FA), FTC and fvPTC compose follicular-pattern thyroid tumors, sharing common mutational prevalence and clinical features [1,2]. Anaplastic thyroid cancer (ATC) is the most advanced and aggressive thyroid cancer and the least likely to respond to treatment [3,4].…”
mentioning
confidence: 99%